Effective l2 language learning opportunities through group work in tertiary level esl class room - Shanmugayogini, R. (university of Jaffna, 2014)
Teaching is an art that incorporates many methods. Second language teachers adopt various strategies to enable the L2 learners to achieve their learning goals. This study explores the possibilities of obtaining effective second language learning opportunities through group work in tertiary level ESL class room. The data were procured from pre and post test performances in group work activities of the first year student from the Faculty of Management and Commerce Studies, University of Jaffna and from the teachers' observation. The objective was to find out whether the group work activities pave the way for Teaching is an art that incorporates many methods. Second language teachers adopt various strategies to enable the L2 learners to achieve their learning goals. This study explores the possibilities of obtaining effective second language learning opportunities through group work in tertiary level ESL class room. effective second language learning opportunities. The findings prove that the participants and the teachers have found that the opportunities of learning in groups increased effective L2 learning opportunities. The study also presents the benefits of using the group work activities in second language classroom.
Keywords: L2 language learning opportunities; Group work; Tertiary level ESL class room